TINDAK PIDANA MENYEBARKAN BERITA BOHONG MERUGIKAN KONSUMEN MELALUI MEDIA SOSIAL INSTAGRAM - Bella Annisa Maharani; Ermania Widjajanti (Fakultas Hukum Universitas Trisakti, 2023)
Online fraud is when a writer accesses a website using internet services with the intention of fooling one of the people he intends to target. As a result, lawmakers must be more aggressive in punishing those who commit fraud, particularly online fraud, by having a deterrent effect on others who do so. 1) Did the Respondent's activities satisfy the criteria listed in Article 45A Paragraph (1) of the Electronic Transaction Information Law Number 19 of 2016 (Research Decision Number 1085/pid.sus/2020/PN.bdg)? This is the problem formulation for this final work; 2) How do judges penalize those who commit online fraud using the social media platform Instagram (analysis of decision No. 1085/Pid.sus/2020/PN.Bdg). With secondary data and qualitative analysis, this form of study is normative, and inferential reasoning is used to arrive at findings. Conclusion: 1) The respondent's conduct satisfy the conditions outlined in Article 45A (1); 2) based on the judge's sentencing in that case, which was based only on theory, particularly contemporary, which combines all three types of sentencing theories-absolute, relative, and a combination of the two-and must satisfy the following criteria: Deterrence, education, rehabilitation, social control, rehabilitation, restorative justice.